Bilingual education in Colombia: towards a recognition of languages, cultures and identities - Mejía, Anne-Marie (Colombian Applied Linguistics Journal, 2006)
In Colombia, there is a tendency to focus on English-Spanish bilingualism at the expense of bilingualism in other foreign languages, or in indigenous languages. This article will argue that there is a need for an equitable language policy which includes all the languages and cultures represented in the country. In addition, we will consider how far bilingual education programmes for majority language speakers in Colombia today actively help towards the creation of a more tolerant society. We will end by indicating implications for future developments.